2019
DOI: 10.1093/neuros/nyz356
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness of the Pipeline Flex Embolization Device With Shield Technology for the Treatment of Intracranial Aneurysms: Midterm Results From a Multicenter Study

Abstract: BACKGROUND The safety and efficacy of the first generation of the Pipeline Embolization Device (PED; Medtronic Inc) have been proven in large case series. Ischemic events are one of the most common complications following treatment of aneurysms with flow diverters. The new PED Flex with Shield technology (PED Shield; Medtronic Inc) was introduced to minimize the rate of complications. OBJECTIVE To evaluate the outcomes of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…At 6 months of follow-up we report no significant in-stent stenosis or intraluminal hyperplasia, with all cases having less than 25% reduction in the intraluminal diameter. This low rate of stenosis is comparable to previous multicentre studies using the Pipeline Flex with Shield Technology, which reported significant stenosis in 19.4% (7/36) 10 and 2.9% (2/69) of cases 11 and correlates with a recent porcine study which found reduced in-stent stenosis when comparing Pipeline Shield with Pipeline Flex. 27 Clinical studies on previous generations of the Pipeline device showed that 8% of cases had at least moderate (>50%) stenosis in comparison to none of the cases in this series.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…At 6 months of follow-up we report no significant in-stent stenosis or intraluminal hyperplasia, with all cases having less than 25% reduction in the intraluminal diameter. This low rate of stenosis is comparable to previous multicentre studies using the Pipeline Flex with Shield Technology, which reported significant stenosis in 19.4% (7/36) 10 and 2.9% (2/69) of cases 11 and correlates with a recent porcine study which found reduced in-stent stenosis when comparing Pipeline Shield with Pipeline Flex. 27 Clinical studies on previous generations of the Pipeline device showed that 8% of cases had at least moderate (>50%) stenosis in comparison to none of the cases in this series.…”
Section: Discussionsupporting
confidence: 88%
“…This study contributes further data to the growing body of evidence that the Pipeline Shield is an effective and safe treatment option for unruptured intracranial aneurysms. A multicentre study has previously shown that use of this device has led to no major strokes or deaths at one year follow-up in a cohort of 50 patients, 10 while a larger study of 151 patients reported two major strokes, one haemorrhage and one death 11 – an acceptable complication rate of 2.6% comparable with meta-analyses of studies involving the second generation Pipeline. 20 This study corroborates these positive findings with observational 6-month follow-up results from a separate tertiary centre for interventional neuroradiology not involved in previous trials.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…High rates of complete occlusion (70.8% and 77.2% at 6 months and 1 year, respectively) and low rate of retreatment (0.05%) among subjects treated with the PED-Shield in the present study are comparable to two previous studies of the PED-Shield: the PFLEX study, which reported complete aneurysm occlusion in 82% of subjects at 1 year and no target aneurysm recurrence or retreatment after complete occlusion, 23 and an observational study that noted complete aneurysm occlusion in 79.7% and 85.3% of cases at 6 months and 1 year, respectively. 24 Our findings are also consistent with reports evaluating previous generations of the PED, which indicated complete occlusion rates ranging from 73.6% to 78.6% at 6 months and from 78.9% to 86.8% at 1 year. 25 Additionally, studies of similar aneurysm sizes including the PREMIER 14 and IntrePED studies 15 reported target aneurysm retreatment rates at 1 year of 2.9% and 1.9%, respectively.…”
Section: Discussionsupporting
confidence: 92%